2021
DOI: 10.48550/arxiv.2111.00117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holomorphic representation of quantum computations

Abstract: We introduce a model of computing on holomorphic functions, which captures bosonic quantum computing through the Segal-Bargmann representation of quantum states. We argue that this holomorphic representation is a natural one which not only gives a canonical definition of bosonic quantum computing using basic elements of complex analysis but also provides a unifying picture which delineates the boundary between discrete-and continuous-variable quantum information theory. Using this representation, we show that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 98 publications
(218 reference statements)
0
7
0
Order By: Relevance
“…For example, it has been shown that negativity of the Wigner function is one of such necessary resources [30,31], albeit not sufficient [32]. More recently, it became clear that squeezing and entanglement also play an important role in the hardness of some sampling problems, but only when combined in the right way [33,34]. In Gaussian Boson Sampling, for example, the state at hand is an entangled Gaussian state, which can be described using a positive Wigner function, while negativity of the Wigner function is provided by the non-Gaussian photon detectors.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, it has been shown that negativity of the Wigner function is one of such necessary resources [30,31], albeit not sufficient [32]. More recently, it became clear that squeezing and entanglement also play an important role in the hardness of some sampling problems, but only when combined in the right way [33,34]. In Gaussian Boson Sampling, for example, the state at hand is an entangled Gaussian state, which can be described using a positive Wigner function, while negativity of the Wigner function is provided by the non-Gaussian photon detectors.…”
mentioning
confidence: 99%
“…The stellar rank is a faithful and operational non-Gaussian measure [34], as it is invariant under Gaussian unitaries, nonincreasing under Gaussian maps, and it lower bounds the minimal number of non-Gaussian operations (such as photon additions or photon subtractions) necessary to prepare a bosonic state from the vacuum, together with Gaussian unitary operations. Moreover, any state can be approximated arbitrarily well in trace distance by states of finite stellar rank, and an optimal approximating state of a given stellar rank can be found efficiently [37].…”
mentioning
confidence: 99%
See 3 more Smart Citations